Manajemen Komplikasi Nontrombotik Intradialitik pada Pasien Penyakit Ginjal Kronis - DEWI, SARASWATI LAKSMI (Universitas Hang Tuah, 2025)
Management of intradialytic nonthrombotic complications in patients with chronic kidney disease is an essential aspect of hemodialysis care. These complications, such as hypotension, hypertension, DDS, muscle cramps, nausea and itching, can have a significant effect on the patient's well-being. Effective treatment requires a multidisciplinary approach that involves the medical team, patient education, and close monitoring during dialysis sessions. Effective protocols, including fluid volume regulation and the proper use of medications, play a crucial role in reducing the frequency and severity of complications. With the right management strategy, it is hoped that the quality of life of patients can be improved, and the morbidity rate associated with intradialytic nonthrombotic complications can be minimised. Further research is needed to optimise clinical practice and enhance the understanding of these complications.